Application of inflow damming method to reduce water threats in the western part of “Wieliczka” Salt Mine - d'OBYRN, Kajetan; STECKA, Jadwiga (Geology, Geophysics and Environment, 2011)
One of the methods applied to eliminate water hazards in salt mines is to dam water inflow. Proper geological survey and small orogen perforation by the mining excavations in the outflow region are essential in order to succeed. An example of an effective closure of water inflow into mining excavations is the successful handling of an emergency on the western border of the "Wieliczka" Salt Mine in 1959 when water irrupted into the mine while conducting research bore 6-67 towards the West. The outflow was closed with the system of water dams. This paper presents geological and mining conditions in the western borders of levels 5 and 6, rescue work process, construction of the water dams system and also pressure development on dams.